Use the elimination method to solve the following system of equations. 4x – 12y = 0 x + 3y = 7

Question

Use the elimination method to solve the following system of equations.
4x – 12y = 0
x + 3y = 7

in progress 0
Caroline 2 weeks 2021-11-22T00:14:04+00:00 2 Answers 0

Answers ( )

    0
    2021-11-22T00:15:31+00:00

    For this case we have the following system of equations:

    4x-12y = 0\\x + 3y = 7

    To solve, we follow the steps below:

    We multiply the second equation by -4:

    -4x-12y = -28

    We add the equations:

    4x-4x-12y-12y = 0-28

    Equal signs are added and the same sign is placed.

    -24y = -28\\y = \frac {-28} {- 24}\\y = \frac {14} {12} = \frac {7} {6}

    We look for the value of the variable “x”:

    x = 7-3y\\x = 7-3 \frac {7} {6}\\x = 7- \frac {21} {6}\\x = \frac {42-21} {6}\\x = \frac {21} {6}\\x = \frac {7} {2}

    Thus, the solution of the system is:

    (x, y): (\frac {7} {2}; \frac {7} {6})

    Answer:

    (x, y): (\frac {7} {2}; \frac {7} {6})

    0
    2021-11-22T00:15:42+00:00

    Answer:

    x= 7/2        y = 7/6

    Step-by-step explanation:

    4x – 12y = 0

    x + 3y = 7

    Multiply the second by( -4) to eliminate the X variable

    4x – 12y = 0

    -4x -12y=  -28

    ADD BOTH

    -24y=-28

    Divide both by  -24

    y= 28/24

    y=7/6

    Plug y into  second equation

    x + 3y = 7

    x+ 3(7/6) = 7

    x+21/6=7

    x+7/2=7

    x=7-(7/2)

    x=( 14/2) – (7/2)

    x= 7/2

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )